Recruitment of Mesenchymal Stem Cells to Damaged Sites by Plant-Derived Components - Maeda, Akito (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem cells (MSCs) are capable of differentiating into a limited number of diverse cells and secrete regenerative factors that contribute to the repair of damaged tissue. In response to signals emitted by tissue damage, MSCs migrate from the bone marrow and area surrounding blood vessels within tissues into the circulating blood, and accumulate at the site of damage. Hence, MSC transplantation therapy is beginning to be applied to the treatment of various intractable human diseases. Recent medicinal plants studies have shown that plant-derived components can activate cell functions. For example, several plant-derived components activate cell signaling pathways, such as phosphatidylinositol 3-kinase and mitogen-activated protein kinase (MAPK), enhance expression of the CXCL12/CXCR4 axis, stimulate extracellular matrix remodeling, and consequently, promote cell migration of MSCs. Moreover, plant-derived components have been shown to promote recruitment of MSCs to damaged tissues and enhance healing in disease models, potentially advancing their therapeutic use. This article provides a comprehensive review of several plant-derived components that activate MSC migration and homing to damaged sites to promote tissue repair.